Human monocytic ehrlichiosis-associated haemophagocytic lymphohistiocytosis treated successfully with doxycycline and dexamethasone: a case report and review of the literature - Javed, Hafiz; Ahmad, Arfa; Rehman, Abdul; Saad, Mohammed (Journal of the Pakistan Medical Association, 2026)
Human monocytic ehrlichiosis (HME) is a tick-borne infection caused by Ehrlichia chaffeensis. Haemophagocytic lymphohistiocytosis (HLH) is a rare hyperinflammatory syndrome characterized by immune activation, most commonly described in children with primary HLH. HME-induced HLH is an extremely rare clinical entity and treatment recommendations are mostly based on case reports, small case series and expert opinion based on extrapolation of data from children with primary HLH. Hereby, we report the case of a 68-year-old male who presented with symptoms of fever and was diagnosed with HLH secondary to HME. He was treated successfully with a 21-day course of doxycycline 100 mg twice daily and dexamethasone 20 mg once daily for 2 weeks, followed by a gradual taper over the next 6 weeks. This case highlights the potential role of doxycycline in combination with high-dose steroids in the management of patients with HLH secondary to HME. Keywords: Ehrlichiosis, Haemophagoytic Lymphohistiocystosis, Tick-Borne Diseases.